2009
DOI: 10.1002/hep.23180
|View full text |Cite
|
Sign up to set email alerts
|

Farnesyltransferase inhibitors reduce ras activation and ameliorate acetaminophen-induced liver injury in mice #

Abstract: T he liver is important for cellular metabolism and is highly susceptible to drug toxicity. Acetaminophen (APAP) is an analgesic and antipyretic drug that is used extensively for therapeutic purposes. It is readily absorbed by the gastrointestinal tract and metabolized by the cytochrome P450 -dependent mixed-function oxidative enzyme pathway to form a reactive intermediate metabolite, N-acetyl-p-benzoquinone imine (NAPQI), which conjugates with glutathione (GSH) and is further metabolized. However, overdose of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…Farnesylation regulates several protein functions, including membrane localization, activity, and protein interactions. Accumulating studies have reported that inhibition of farnesyltransferase inhibits proinflammatory activities, such as inhibition of NF-〉 and Ras activation (23,28). Here, we show that inhibition of farnesyltransferase protects against M1 protein-provoked lung edema and tissue injury.…”
Section: Discussionsupporting
confidence: 53%
“…Farnesylation regulates several protein functions, including membrane localization, activity, and protein interactions. Accumulating studies have reported that inhibition of farnesyltransferase inhibits proinflammatory activities, such as inhibition of NF-〉 and Ras activation (23,28). Here, we show that inhibition of farnesyltransferase protects against M1 protein-provoked lung edema and tissue injury.…”
Section: Discussionsupporting
confidence: 53%
“…The CTGF-initiated PI3-K and Akt activation was blocked by the PI3-K inhibitor wortmannin. The CTGF-stimulated Ras, ERK1/2, PI3-K and Akt activation were all abolished by manumycin A, a Ras activation inhibitor (farnesyltransferase inhibitor) [38]. Similarly, pretreatment of the cells with LXA 4 partially but significantly downregulated CTGF-initiated activation of Ras, ERK1/2, PI3-K and Akt.…”
Section: Resultsmentioning
confidence: 99%
“…These findings are in agreement with previous reports showing in isolated hepatocytes and in vivo that a massive chemical-induced oxidant stress leads to JNK activation (Czaja et al, 2003; Conde de la Rosa et al, 2006; Hong et al, 2009). However, the oxidant stress most likely does not activate JNK directly, but targets upstream events such promoting either the dissociation of thioredoxin and apoptosis signal-regulating kinase 1 (ASK1) (Nakagawa et al, 2008) or the Ras pathway (Saha and Nandi, 2009). Alternatively, JNK can be released from a complex with glutathione-S-transferase Pi (GST-Pi) by binding of NAPQI to GST (Elsby et al, 2003).…”
Section: Discussionmentioning
confidence: 99%